KETERLIBATAN AYAH DAN KAITANNYA DENGAN EMOTIONAL WELL-BEING PADA REMAJA AKHIR - SILVIANA, SILVIANA; HASTUTI, RAHMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study aims to determine the relationship between father involvement and emotional well-being in late adolescents. Emotional well-being is a psychological condition that plays an important role for individuals, especially in late adolescents. Individuals with positive emotional well-being will be more capable of experiencing life satisfaction, conversely, if emotional well-being is low, their lives will be dominated by feelings of dissatisfaction. The participants in this study are late adolescents aged 18-24 years. The sampling technique used in this research the non-probability purposive sampling technique, with a total of 305 participants in this study. The measurement tool used for the father involvement variable is the Perception of Father’s Involvement (PFI), while the measurement tool for the Emotional well-being variable is the Positive and Negative Affect Schedule. (PANAS-SF). The correlation analysis in this study used Spearman's non-parametric correlation, and the results showed a significant positive relationship between father involvement and emotional well-being among late adolescents. (r = 0.429, p 0.000<0.05). This indicates that the higher the father involvement, the higher the emotional well-being. ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara keterlibatan ayah dengan kesejahteraan emosional pada remaja akhir. Emotional well-being merupakan kondisi psikologis yang berperan penting bagi individu khususnya pada remaja akhir. Individu dengan Emotional well-being yang positif akan lebih mampu merasakan kepuasan hidupnya, begitupun sebaliknya jika Emotional well-being rendah maka hidupnya akan didominasi oleh rasa ketidakpuasan. Partisipan penelitian ini adalah remaja akhir berusia 18-24 tahun. Teknik pengambilan sampel yang digunakan yakni teknik non-probability purposive sampling, total partisipan pada penelitian ini berjumlah 305. Alat ukur yang digunakan untuk variabel Father Involvement adalah Perception of Father’s Involvement (PFI), sedangkan pada variabel Emotional well-being adalah Positive and Negative Affect Schedule (PANAS-SF). Analisis korelasi pada penelitian ini menggunakan korelasi non-parametic Spearman hasil menunjukkan bahwa adanya hubungan positif yang signifikan antara keterlibatan ayah dengan kesejahteraan emosional pada remaja akhir. (r = 0.429, p 0.000<0.05) Hal ini menunjukkan bahwa semakin tinggi keterlibatan ayah maka Emotional well-being juga akan tinggi.